A balanced analytical look at the term, limit, and provisions of the actor In Sibawayh's book (Journal of the College of Basic Education, 2022)
The hadeeth in this research came to clarify the nature of presenting the subject of the subject in Sibawayh’s book and understanding it as a definition, terminology, and rulings, with reference to some of the opinions of the scholars who came after it. The association of the meanings that aroused the interest of its author, so we see him talking about the conditions of the verb with its subject, as a reminder and a femininity when he talks about the ambiguous adjective.